2002
DOI: 10.1103/physrevb.66.195407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth rate on the spatial distributions of dome-shaped Ge islands on Si(001)

Abstract: Ge/Si͑001͒ layers are grown by gas-source molecular beam epitaxy at 600°C to probe island self-ordering phenomena. We vary the Ge growth rate by a factor of 40, 1.2-47 monolayers ͑ML͒ min Ϫ1 , and adjust the Ge coverage, 5.9-8.9 ML, to produce films consisting primarily of dome-shaped Ge islands. Measurements of the radial and nearest-neighbor distributions are compared to calculated distributions for random arrangements of circular islands. At low growth rates, island formation is inhibited at small separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…The diameters of the islands are smaller than that grown by depositing SiGe layer on Si observed above. Note that the critical thickness (1.8 nm) of the islands fabricated by IBSD technique is larger than that fabricated by MBE and CVD techniques [24,25,26]. Our previous results indicated that the μc-Si buffer layer and the higher kinetic energy of the sputtered Si and Ge atoms may explain this phenomenon [10,12].…”
Section: Page 13 Of 33mentioning
confidence: 76%
“…The diameters of the islands are smaller than that grown by depositing SiGe layer on Si observed above. Note that the critical thickness (1.8 nm) of the islands fabricated by IBSD technique is larger than that fabricated by MBE and CVD techniques [24,25,26]. Our previous results indicated that the μc-Si buffer layer and the higher kinetic energy of the sputtered Si and Ge atoms may explain this phenomenon [10,12].…”
Section: Page 13 Of 33mentioning
confidence: 76%
“…9, reveal sublinear (~0.50) power exponents for both P1 and P2 bands. Sublinear power exponentfs with a power exponent of~0.78 have previously been attributed to a type-II band alignment with a limited density of localized states for excitons [4,15]. An increase of localization of the radiative centers would lead to a smaller power exponent.…”
Section: Photoluminescence Of Ge Nanoclustersmentioning
confidence: 96%
“…As already mentioned foremost, without the presence of a Xe buffer layer, Ge growth on Si(100) is well known to form SK clusters [13][14][15] in the absence of a Xe buffer layer. Strain-driven SK growth proceeds in two steps.…”
Section: Morphology and Structure Of Ge Nanoclustersmentioning
confidence: 97%
“…To explore the possibilities, Cahill and Greene employ laser processing to modify surfaces and films [53,54,55,56] . A recent experiment on the controlled pulsed illumination of thin thermally-grown oxide layers on Si has shed light on the process of delamination by thermal stress due to differential expansion [57] .…”
Section: Driven Systemsmentioning
confidence: 99%